ASSESSMENT AND IDENTIFICATION OF POLYOL BASED ON PALM OIL AND NATURAL FILLING MATERIALS FOR RENEWABLE COATING PAINT APPLICATION - Rihayat, Teuku; Syafruddin; Ismy, Adi Saputra; Aidy, Nurhanifa; Izza, Nurul (International Journal of Research -GRANTHAALAYAH, 2022)
Chitosan/clay hybrid nanoparticles have been prepared as natural antibacterial and anticorrosion agents to enhance the protective function of polyurethane-based coating paints. Chitosan is a material with antibacterial properties because it contains acetamide group which is widely used for hygiene purposes in the medical field. Clay is a natural clay particle with a hollow structure that allows loading and release of active substances such as surfactant ions that can contribute to improving the properties of the material. The polyurethane in this study was obtained from palm oil oleic acid, which was processed into polyol, toluene diisocyanate was added to produce polyurethane. Coating paint is efficiently loaded with chitosan and clay active substances which are combined to form a hybrid composite. Based on the FTIR data of polyurethane showing the formation of a hydroxyl group on the palm oil epoxide compound, the reaction lasted for 2 hours at 60oC as evidenced by the absorption of the OH wave number which widened at 3305.99 cm-1. The value of the wavelength of the OH group in the bentonite sample before and after purification has decreased, proving that the intercalation of surfactants into the bentonite interlayer causes the hydrophilic nature of bentonite to change to hydrophobicity. The d-spacing layer of raw bentonite has a maximum reflection angle peak of 7.26o with a d-spacing value of 1.132 nm, and the d-spacing size increases to 1.631 nm at the peak of the maximum reflection angle of 4.49o after purification. The presence of absorption at 1064.71 cm-1 in shrimp shell chitosan indicates COC vibration.